Impacts of safety on the design of light remotely-piloted helicopter flight control systems. (May 2016) - Di Rito, G.; Schettini, F.
Abstract: This paper deals with the architecture definition and the safety assessment of flight control systems for light remotely-piloted helicopters for civil applications. The methods and tools to be used for these activities are standardised for conventional piloted aircraft, while they are currently a matter of discussion in case of light remotely-piloted systems flying into unsegregated airspaces. Certification concerns are particularly problematic for aerial systems weighing from 20 to 150 kgf, since the airworthiness permission is granted by national authorities. The lack of specific requirements actually requires to analyse both the existing standards for military applications and the certification guidelines for civil systems, up to derive the adequate safety objectives. In this work, after a survey on applicable certification documents for the safety objectives definition, the most relevant functional failures of a light remotely-piloted helicopter are identified and analysed via Functional Hazard Assessment. Different architectures are then compared by means of Fault-Tree Analysis, highlighting the contributions to the safety level of the main elements of the flight control system (control computers, servoactuators, antenna) and providing basic guidelines on the required redundancy level. Highlights: A method for architecture definition and safety assessment of light RW‐UAS flight control systems is proposed. Relevant UAS failures are identified and analysed via Functional Hazard Assessment and Fault‐Tree Analysis. The key safety elements are control computers, servoactuators and TX/RX system. Single‐simplex flight control systems have inadequate safety levels. Dual‐duplex flight control systems demonstrate to be safety compliant, with safety budgets dominated by servoactuators.